(3Jbhje fXe GdeYdheGJ HGSJNOGe HMhK GdYedjGJ (B/s - (3GdTgQHdj, EfYGe Ydj Jhajbs ((3YeGf(B: s, 2009)
(3GdfXe,HMhK GdYedjGJ,Jbhje fXe GdeYdheGJ HGSJNOGe HMhK GdYedjGJ,fXGe GdeYdheGJ hMOI GdMGSHI,fXGe GdeYdheGJ hMOI GdhSGFd GdSeYjI hGdHUQjI,GLQGAGJ fXGe GdeYdheGJ hMOI JfejI GdeYdheGJ,hMOI eYdheGJ GdeYGdLI GdafjI,fXGe eYdheGJ hMOI GdeYdheGJ hGdJhKjb ,fXGe eYdheGJ hMOI GdEYGQI,fXGe eYdheGJ hMOI GdOhQjGJ,fXGe eYdheGJ hMOI GdeQGLYs
(3HHdjhZQGajG(B:(3U U(B.446-466s
Keywords: (3HMhK GdYedjGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s